MANY ARE CRYING, "WHO WILL SHOW US ANY GOOD?" - VOICES OF DECEMBER 2007 POST-ELECTION VIOLENCE VICTIMS IN KENYA - Mbutu , Paul; Wanjigi, Jimi (Journal of Public Policy and Administration, 2022)
Purpose: This study analyzes and brings to light the voices of the victims who suffered particularly the socio-economic effects of the 2007 December violence and land clashes that took place in Kenya. During the 2007 December violence and land clashes, women, children and men were affected differently by the conflict, with women and children suffering most of the effects such as death, physical injuries and insufficient resources to take care of their basic needs. Consequently, as women experienced the immediate consequences of the conflict, they were the first to receive humanitarian assistance from international Non-Governmental Organizations (NGOs) like the Red Cross and a few indigenous ones. The voices of the victims narrating the violence they went through and the trauma they lived with would engage the minds of peace-caring persons to speak against violence of this nature in the future. Methodology: Utilizing a qualitative study approach, the study focuses on 17 interview transcripts, statements taken from Kenyan newspapers of January 2008, online newspapers during the same period, eyewitness accounts as recorded in papers. For the theoretical framework, I used thematic analysis because these were stories "told" by the affected individuals. Findings: My aim was to purposely establish how the rhetorical narratives as told by the affected individuals "chain out". Are there any running main themes and patterns across the narratives? What is the "master narrative? What are the "counter narratives", how are they constructed, and how do they attack the master narrative? One of the key issues I identified in my literature review as the cause of violence in Kenya is land. Violence was rampant and severe in the rich agricultural region of the Rift Valley. Unique contribution to Theory, Policy and Practice: The study underscores the importance of listening to people's voices and the stories as told by the victims themselves. Narrative framework and mainly thematic analysis framework helped in the analysis of the stories told by the violence victims. The country seemed to be polarized along ethnic lines - which to me, is a big deterrent for development. Politically, people need to be educated on their political rights and not be misused by politicians for their own advantage. The government, the judicial system, the church and the Electoral Commission of Kenya should address the issues raised by these traumatized and overwhelmed individuals.